Diverse Enzymes With Industrial Applications in Four Thraustochytrid Genera - Lin, Hsiu-Chin; Li, Wei-Hao; Chen, Chi-Chih; Cheng, Tien-Hsing; Lan, Yu-Hsuan; Huang, Ming-Der; Chen, Wen-Ming; Chang, Jo-Shu; Chang, Hsin-Yang (Frontiers in Microbiology, 2020)
Thraustochytrids are heterotrophic fungus-like protists that can dissolve organic matters with enzymes. Four strains, AP45, ASP1, ASP2, ASP4, were isolated from the coastal water of Taiwan, and respectively identified as Aurantiochytrium sp., Schizochytrium sp., Parietichytrium sp., and Botryochytrium sp. based on 18S rRNA sequences. Transcriptome datasets of these four strains at days 3-5 were generated using Next Generation Sequencing technology, and screened for enzymes with potential industrial applications. Functional annotations based on KEGG database suggest that many unigenes of all four strains were related to the pathways of industrial enzymes. Most of all four strains contained homologous genes for 15 out of the 17 targeted enzymes, and had extra- and/or intra-cellular enzymatic activities, including urease, asparaginase, lipase, glucosidase, alkaline phosphatase and protease. Complete amino sequences of the first-time identified L-asparaginase and phytase in thraustochytrids were retrieved, and respectively categorized to the Type I and BPPhy families based on phylogenetic relationships, protein structural modeling and active sites. Milligram quantities of highly purified, soluble protein of urease and L-asparaginase were successfully harvested and analyzed for recombinant enzymatic activities. These analytical results highlight the diverse enzymes for wide-range applications in thraustochytrids.